Effects of Negative Utterances on Mental Health of Grade 11 Home Economic Students: An Emerging Guide (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The words that we say are extremely powerful. Words can bring positivity but can also be dangerous and harmful. Words can purposely criticize, insult, or denounce someone else. Words can also cause low self-esteem and hurt others mentally and emotionally, which can also lead to depression and even suicide. Negative utterances can be teasing, taunting, profanities, name-calling, sexual remarks, blaming, accusations, spreading rumors, and even threats. The sources of negative utterances can vary from social media, friends, relatives, school, and even one's own family. Sampling method, instrument, and data gathering procedure and analysis were used to serve as the basis in the interpretation of the study. The respondents of the study were 50Grade 11 Home Economics students of Bestlink College of the Philippines, S.Y. 2019–2020. The gathered data from 50 sets of questionnaires completed the needed information. The researchers analyzed and evaluated the result of the study. The respondents answered that profane language is the most common negative utterances that they experienced, with a composite weighted mean of 2.8 or verbal interpretation of "sometimes." The majority of these utterances were from their school friends with a weighted mean of 3.5 or often. The data also showed that negative utterances had a moderate effect on how the respondents perceive themselves, how they feel about themselves, and how they communicate, with a composite weighted mean of 2.4. These results showed that the negative utterances the respondents have experienced affected their mental health. Students’ further knowledge and awareness of the causes and importance of mental health can prevent the negative effects on their mental health. Student’s positive behavior is also important; learning how to accept constructive criticism can help to improve themselves.
Keywords: negative utterances, mental health, awareness